Introduction to Islamic and Buddhist Personal Ethics - Mohd Rosmizi Abd Rahman (Universiti Sains Islam Malaysia, 2022)
The Islamic and Buddhist concepts and views on ethics in this book have been descriptively discussed, analysed and compared. The personal codes of ethics of both religions have also been extensively elucidated.